MUSLIM COMMUNITIES OF THE ROSTOV REGION - PATEEV, Rinat (CENTRAL ASIA AND THE CAUCASUS, 2006)
Avast body of works has recently appeared by Russian social scientists who look into the dynamics of religious revival and re-Islamization in Russia. They mainly concentrate on administrative units with autochthonous Muslim populations, conflict areas, and non-Muslim regions, some of them fairly developed economically, which have found themselves at the receiving end of the “migration assault.” There are territories with predominantly Russian-speaking populations which, while subjected to migration pressure, have never experienced obviously ethnic-related problems. The Rostov Region (about which much less has been written1) is one such place: this does not mean, however, that it does not have its share of dynamics in ethnic and confessional relationships. There are such dynamics, which call for a detailed investigation to obtain a clearer picture of the changes in the ethnic and religious balance on the Don. Shortage of empirical data has forced me to combine traditional sources with the participant observer method and information from regional Internet publications and the local media. Meetings with members of Muslim communities of Rostov and the Rostov Region, as well as contacts with regional bureaucrats responsible for ethnic policies also provided a wealth of information.